Rotational pulsed triboelectric nanogenerators integrated with synchronously triggered mechanical switches for high efficiency self-powered systems. (April 2021) - Shang, Wanyu; Gu, Guangqin; Zhang, Wenhe; Luo, Hongchun; Wang, Tingyu; Zhang, Bao; Guo, Junmeng; Cui, Peng; Yang, Feng; Cheng, Gang; Du, Zuliang
Abstract: With the merits of zero internal equivalent resistance and maximized output energy, the pulsed mode triboelectric nanogenerators (TENGs) can achieve impedance matching with the power management circuits (PMCs), showing wide application prospects in self-powered systems. The key for developing Pulsed-TENGs lies in designing synchronously triggered mechanical switches (STMSs). However, rotational TENGs, as a promising configuration for harvesting mechanical energy, have rarely been designed as pulsed mode because of the difficulty in fabricating rational STMSs. Herein, rotating freestanding triboelectric-layer Pulsed-TENGs (RF-Pulsed-TENGs) are realized through integrating STMSs on triboelectric layers in one step by printed circuit board process. Since the on-off states of the STMSs can match well with the rotation frequency, the output voltage and energy of the RF-Pulsed-TENGs are maximized regardless of the rotation frequency or load resistance. Both alternating current and unidirectional current output RF-Pulsed-TENGs have been realized, and the energy storage efficiency of their corresponding passive PMCs can reach 51.6% and 52.0%, respectively. The system consisting of a gearbox, a passive PMC, and a RF-Pulsed-TENG has been demonstrated to power a range of electronic devices, such as calculators, electronic watches, and temperature/humidity meters, offering significant advantages and promising applications in efficient mechanical energy harvesting and self-powered sensing. Graphical Abstract: Rotational freestanding triboelectric-layer mode pulsed triboelectric nanogenerators (RF-Pulsed-TENGs) based on synchronously triggered mechanical switches that integrated on the electrode layer are developed. The output voltage and energy of the RF-Pulsed-TENGs can keep maximized regardless of rotation frequency or load resistance. The system consists by gearbox, efficient passive PMCs, and RF-Pulsed-TENGs show application prospects in self-powered systems. ga1 Highlights: Rotational Pulsed-TENGs have rarely been developed because of the difficulty in designing rational STMSs. Rotating freestanding Pulsed-TENGs (RF-Pulsed-TENGs) are realized through integrating STMSs on electrode layer. Both alternating current and unidirectional current RF-Pulsed-TENGs are realized. The on–off states of the STMSs can match well with the rotation frequency of the RF-Pulsed-TENGs. A self-powered system consisting of gearbox, efficient passive PMC, and an RF-Pulsed-TENG has been demonstrated.